PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM PERJANJIAN ELEKTRONIK LAYANAN JASA PENGANGKUTAN - Bagiartha W, I Putu Pasek (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2020)
Attachment of legal subjects in the transportation services of Gojek refers to econtracts which are divided into 2 types of agreements, namely partnership agreementsbetween Gojek and Gojek Partners and transportation agreements between Gojek Partnersand consumers. To guarantee the fulfillment of rights and obligations in the implementationof the agreement, the legal protection provided is oriented to preventive and repressive forms.Preventive form is by giving regulations, and repressive emphasis is by the law enforcementin the level of state administrative law, criminal law, and civil law. However, this conditiondoes not completely prevent the emergence of disputes, which in Gojek Code of Conductmentions 2 types of Gojek Partner violations as causes of disputes namely violations reportedby consumers and violations detected by the system, both in the low, medium, high, veryhigh and maximum very high categories. The cause of consumer disputes is generallyreflected in the form of complaints based on an assessment of service quality in terms oftangible, reliability, responsiveness, assurance, and empathy, which demand to be resolvedeither through deliberation or through court.